Faktor Yang Mempengaruhi Kepatuhan Membayar PBB di Surakarta - Susilawati, Wiwin; Ismunawan, Ismunawan (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of tax services, tax sanctions, knowledge, and income on taxpayer compliance in paying land and building taxes. Questionnaires were distributed to 100 respondents who were distributed randomly. The sampling technique used in this research is accidental sampling. The data analysis used is the test instrument data including validation test and reliability test, classical assumption test includes normality test, multicollinearity and hesteroscedasticity test, and hypothesis testing includes t test, f test and R2 test. The results of testing tests that all of the variables tested have no significant effect on taxpayer compliance. Tax and tax variables have a significant effect on taxpayer compliance in paying land and building taxes in Surakarta. While knowledge and income have no effect on taxpayer compliance in paying land and building taxes in Surakarta.